2017
DOI: 10.7127/rbai.v11n700681
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINAÇÃO DO COEFICIENTE DE CULTIVO DA CULTURA DO PIMENTÃO (Capsicum anuum) POR MEIO DO LISÍMETRO DE DRENAGEM

Abstract: RESUMOObjetivou-se com este trabalho instalar e operar lisímetros de drenagem para determinar o coeficiente de cultivo (Kc) da cultura do pimentão na região Agreste DETERMINATION OF THE CROP COEFFICIENT OF SWEET PEPPER (Capsicum anuum) BY MEANS OF DRAIN LYSIMETER ABSTRACTThe objective of the work installed and operate drainage lysimeters to determine the crop coefficient (Kc) of the sweet pepper crop in the Agreste region of the state of Alagoas. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The average values obtained for conventional tillage were close to those observed in the present study; however, water consumption was higher since the crop cycle was longer. Silva et al (2017) observed a total consumption of 530 mm for the bell pepper and an average of 6.6 mm d -1 in Arapiraca, AL, Brazil, during a 150-day cycle. Albuquerque et al (2012) reported a mean ETc of 1.97 mm d -1 and a total water consumption of 206.85 mm over 105 DAT for the bell pepper crop cultivated in fields in Recife, PE, Brazil.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The average values obtained for conventional tillage were close to those observed in the present study; however, water consumption was higher since the crop cycle was longer. Silva et al (2017) observed a total consumption of 530 mm for the bell pepper and an average of 6.6 mm d -1 in Arapiraca, AL, Brazil, during a 150-day cycle. Albuquerque et al (2012) reported a mean ETc of 1.97 mm d -1 and a total water consumption of 206.85 mm over 105 DAT for the bell pepper crop cultivated in fields in Recife, PE, Brazil.…”
Section: Resultsmentioning
confidence: 91%
“…In addition to crop-related aspects under specific climatic conditions, determining the reference evapotranspiration may interfere with kc values. Silva et al (2017) found mean kc values corresponding to 1.05 (phase II) and 1.41 (phase III) by applying the Hargreaves-Samani method to estimate ET 0 . Nonetheless, they stated that this method overestimates the kc values compared with the Penman-Monteith-FAO method, which were 0.81 (phase II) and 1.05 (phase III).…”
Section: Resultsmentioning
confidence: 98%